A Study of Acclimatization Media on Strawberry (Fragaria x ananassa Duch.) Plantlets Produced from Meristem Culture - Rindang Dwiyani; Yuyun Fitriani; Francis Geren Sta Ana; Putu Oki Bimantara (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2024)
Acclimatization is the final stage of propagation by in vitro culture. This phase is crucial in micropropagation, as it will determine the survival of plantlets outside culture jars. This phase’s efforts should ensure optimal conditions, including the media type. This study sought the best media for acclimating strawberry plantlets produced under meristem culture. The research employed the randomized block design, utilizing 7 various media treatments, which include husk charcoal; perlite; cocopeat; perlite + husk charcoal; soil + sand; husk charcoal + cocopeat; and perlite + cocopeat. The media mix was set at 1:1 a ratio (weight/weight), with 9 replicates. The chemical properties of the media were then analyzed, including several parameters such as organic C, total N, and water content. Several parameters were observed for plantlet’s growth parameters, including plant survival rates, number of leaves per plant, average leaf area, and root fresh weight. The results found that cocopeat was the best medium for acclimating strawberry plantlets. In cocopeat media, the plant survival rate reached 96.68%, with the leaves number of 7.67 plant-1, an average leaf area of 120.92 cm2 plant-1, and root fresh weight of 4.30 g plant-1. These results indicate that cocopeat is a medium derived from coconut fiber powder, a natural resource that can be renewed sustainably and produces better plant plantlet growth.